Anti-inflammatory and protective effects of Pimpinella candolleana on ulcerative colitis in rats: a comprehensive study of quality, chemical composition, and molecular mechanisms - Liu, Xiaoqi; Xiao, Hai; Luo, Mingxia; Meng, Junpeng; Zhong, Lin; Wu, Tao; Zhao, Yongxia; Wu, Faming; Xie, Jian (Frontiers in Pharmacology, 2024)
Introduction: PPimpinella candolleana Wight et Arn. is a traditional Chinese herbal medicine used by the Gelao nationality in southwest China. This study aimed to determine the quality and chemical composition of P. candolleana and to identify its potential therapeutic targets and mechanisms in acetic acid-induced ulcerative colitis (UC) rats through integrated approaches. Methods: Morphological and microscopic characteristics, TLC identification, and quantitative analysis of P. candolleana were performed.UPLC-Q-TOF-MS, network pharmacology, and molecular docking were used to identify its chemical composition and predict its related targets in UC. Furthermore, a rat model was established to evaluate the therapeutic effect and potential mechanism of P. candolleana on UC.Results: Microscopic identification revealed irregular and radial arrangement of the xylem in P. candolleana, with a light green cross-section and large medullary cells.UPLC-Q-TOF-MS detected and analyzed 570 metabolites, including flavonoids, coumarins, and terpenoids. Network pharmacology identified 12 effective components and 176 target genes, with 96 common targets for P. candolleana-UC, including quercetin, luteolin, and nobiletin as key anti-inflammatory components. GO and KEGG revealed the potential involvement of their targets in RELA, JUN, TNF, IKBKB, PTGS2, and CHUK, with action pathways such as PI3K-Akt, TNF, IL-17, and apoptosis. Molecular docking demonstrated strong affinity and binding between these key components (quercetin, luteolin, and nobiletin) and the key targets of the pathway, including JUN and TNF. Treatment with P. candolleana improved body weight loss, the disease activity index, and colonic histological damage in UC rats. P. candolleana also modulated the levels of IL-2 and IL-6 in UC rats, reduced the expression of pro-inflammatory cytokines such as IL-6, MAPK8, TNF-α, CHUK, and IKBKB mRNA, and decreased the expression of TNF, IKBKB, JUN, and CHUK proteins in the colon of UC rats, thereby reducing inflammation and alleviating UC symptoms.Conclusion: P. candolleana exerts its protective effect on UC by reducing the expression of proinflammatory cytokines and inhibiting inflammation, providing scientific evidence for its traditional use in treating gastrointestinal diseases. This study highlights the potential of P. candolleana as a natural therapeutic agent for UC and contributes to the development of novel medicines for UC treatment.